Enhancement of Wound Healing Efficiency Using Fish Scale Gelatin Combined with Silk Sericin - Pornrapat Uchibori; Pimpida Nangkam; Pakaporn Sanchia; Kanitkarn Petchkoh Tuntrirat; Lizexin Hu; Viwat Sutana (Malaysia Journal of Invention and Innovation, 2024)
Our project focused on creating a natural wound dressing by blending gelatin extracted from Nile tilapia fish scales with herbal extracts, particularly turmeric. The goal was to address issues like excessive bleeding and bacterial infections, especially those caused by drug-resistant strains like Staphylococcus aureus. By harnessing the healing power of curcumin, the key component in turmeric, known for its antibacterial and anti-inflammatory properties, we developed a hydrogel that promotes faster healing while also preventing infections. To make the dressing, we extracted gelatin from the fish scales using a mild acid solution and incorporated calcium chloride to strengthen the structure of the hydrogel. This made the material more durable and practical for wound care. We tested its ability to fight bacteria, stop bleeding, and help wounds heal more quickly. Our results were promising. The hydrogel successfully stopped bleeding in a short time and promoted significant cell migration, which means it helps wounds heal faster. Additionally, it demonstrated strong antibacterial properties, effectively inhibiting the growth of S. aureus. Overall, this project highlights the potential of using natural and sustainable materials in medical applications. The combination of fish scale gelatin and herbal extracts created a multifunctional wound dressing that not only speeds up the healing process but also protects against.